AMFI's Reality School: A circular economy agenda for fashion education. Issue 1 (1st April 2018) - Hall, Nicholas; Velez-Colby, Fiona
The circular economy (CE) agenda is gaining traction within the fashion industry and increasingly within fashion education. It provides a connective, interdisciplinary framework that offers a roadmap for transition towards a sustainable economy. As business eco-systems re-align to meet new standards of ethical and sustainable practice for the fashion industry, a new agenda for fashion education emerges: one of circularity. This article evaluates Amsterdam Fashion Institute's (AMFI) Reality School concept, examining how CE education is being embedded within it and the levels of integration achieved. It argues that a CE approach to curriculum design can motivate deep learning through experimental practice, deep-dive research and systems thinking. It provides a structural framework of a CE agenda to fashion education curriculum, establishing a novel approach that could be applied to other specialist fashion education institutions.